"I Heard That Voice at Troy": Resonance at The Other Place in Derek Walcott's The Odyssey: A Stage Version. (23rd March 2018) - Reed, Ethan
Abstract : I examine the international structures of collaboration behind the first theatrical production of Derek Walcott's The Odyssey: A Stage Version with the Royal Shakespeare Company in Stratford-upon-Avon, July 1992. Reconsidering this play's production in the context of colonial history, I argue, reveals ways in which The Odyssey foregrounds the constraints of its initial production circumstances in moments of meta-theatrical dissonance. In an effort to account for the temporality of production, diachronic literary object, and the trans-historical preoccupations of the work itself, I adopt Wai Chee Dimock's "theory of resonance" to the context of postcolonial theatrical production. Through this lens, theatrical spaces like The Other Place become resonance chambers where resonances of all sorts—be they literary, as with allusions to Joyce's Ulysses, historical, colonial, spatial, or even physical—reverberate not only with the institutions that structure them, but the affective dimensions of performance through which they are staged and embodied.